A Cross-sectional study: The Relationship of Family Support Toward Level Adherence Therapy and Hospitalization in Outpatient Treatment of Schizophrenia - Dwi Aulia Ramdini; Melisa Intan Barliana; Nanda Restiana; Citra Yuliyanda Pardilawati; Ramadhan Triyandi; Nurma Suri; Yulianasari Pulungan (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2025)
Adherence is one of the essential components in the management of schizophrenia. However, adherence levels remain suboptimal, ranging from 20-89%. Multiple factors, including sociodemographic characteristics and family support have been reported to influence medication adherence and hospitalization rates. This study aimed to investigate relationship between family support, medication adherence, and hospitalization among patients with schizophrenia at the Mental Health Hospital Lampung Province. A cross-sectional study design was employed, and data were collected through patient interviews. Medication adherence was assessed using the Medication Adherence Rating Scale (MARS), while family support was measured using validated and reliability-tested family support questionnaire. A total of 106 patients met the inclusion criteria, of whom 65% demonstrated high levels of medication adherence. The factor including sex (p=0,047), employement status ( p=0,004), and family support (p<0.000) were significantly associated with medication adherence. In addition, age (p=0.019), family support (p<0.001), and medication adherence (p<0,000) were significantly associated with hospitalization. These findings indicate that family support has a positive influence on medication adherence and serves as a protective factor againts at worsening prognosis, as reflected by reduced hospitalization. This study emphasizes the crucial role of family support in achiving successful treatment outcomes in patients with schizophrenia.